Nilai Sosial dan Nilai Moral dalam Novel Bukan Pasar Malam Karya Pramoedya Ananta Toer serta Relevansinya dengan Pembelajaran Bahasa dan Sastra di SMA - Mega Fiyani (PROSIDING SEMINAR NASIONAL PENDIDIKAN, BAHASA, SASTRA, SENI, DAN BUDAYA, 2022)
The purpose of this research is to: 1) is to find out the structure of the novel (characters, plot, and setting) that builds the storytelling in the novel Bukan Pasarmalam by Pramoedya Ananta Toer. 2) Is to know the social values contained in the novel Bukan Pasarmalam by Pramoedya Ananta Toer. 3) is to know the moral values in the novel Bukan Pasarmalam by Pramoedya Ananta Toer. 4) is to find out the relevance between the novel Bukan Pasarmalam and learning Indonesian language and literature in high school. This research method uses content analysis method, using a qualitative approach. With the method used, this study found the results that: 1) The structure of the novel Bukan Pasarmalam describes people's lives in Indonesia before and after independence. In this novel, Pramoedya describes the sadness, suffering and difficulties of the post-independence Indonesian people. 2) the findings and results of the analysis of this novel, it is known that the novel Bukan Pasarmalam contains social values through social interactions within the family and society. These values include: the value of affection, the value of compassion, the value of protection, the value of religiosity, the value of caring, the value of equality, the value of togetherness, the value of sincerity. 3) The moral values contained in the character I are in the form of behavior that most are worthy of being an example for everyone such as being responsible, patient, guarding one's tongue, and being religious. 4) The social values and moral values in the novel Bukan Pasarmalam can be relevant to the 2013 curriculum for Indonesian language and literature subjects in class XI high schools, there is material about analyzing the intrinsic and extrinsic elements of literary works, one of which is Indonesian novels which contain values cultural, social, moral, historical, and religious with basic competencies: identifying life values contained in a collection of short stories and analyzing messages from two fiction books (novels and poetry), while the learning materials: short stories, short story contents, values life, short story intrinsic elements, novel elements and reviews of novels.